Highly Controllable Hierarchically Porous Ag/Ag2S Heterostructure by Cation Exchange for Efficient Hydrogen Evolution. Issue 44 (24th September 2021) - Xu, Huajie; Niu, Xiaoxiao; Liu, Zhuangzhuang; Sun, Mingzi; Liu, Zhaodi; Tian, Zhimei; Wu, Xiaoxia; Huang, Bolong; Tang, Yu; Yan, Chun‐Hua
Abstract: Establishing the hierarchical porous architectures has been considered to be the most efficient approach to realize the efficient mass diffusion and large exposed active sites of designed micro/nanomaterial catalysts for hydrogen evolution reactions (HER). In this work, the nonequivalent cation exchange strategy is developed to fabricate the hierarchically porous Ag/Ag2 S heterostructure based on the rapid cation exchange by the metal‐organic framework (MOF)‐derived CoS. The as‐prepared Ag/Ag2 S inherits the original 3D hollow morphology of CoS with porous nature, possessing abundant S‐vacancies and lattice strain simultaneously due to the coordination loss and in‐situ epitaxial growth of metallic Ag on the surface. Owing to the optimizations of lattice and electronic structures, the unique hierarchically porous Ag/Ag2 S heterostructure exhibits superior catalytic performance than previously reported catalysts derived from MOF. Theoretical calculations have confirmed that the co‐existence of Ag cluster and sulfur vacancies activates the electroactivity of the interfacial defective region to boost the HER process. The binding strength of the proton and energetic trend of HER has been optimized with the formation of Ag/Ag2 S heterostructure, which guarantees the efficient generation of H2 . This study opens a new strategy for the utilization of the nonequivalent cation exchange strategy to efficiently synthesize advanced electrocatalysts with high performances. Abstract : In this work, an effective nonequivalent cation exchange strategy is developed for engineering the hierarchically porous Ag/Ag2 S heterostructure, which has shown superior catalytic performance for hydrogen evolution reaction (HER). The heterostructure guarantees efficient electron transfer and alleviates the overbinding effect of protons, leading to a low overpotential of HER and long‐term stability in the acidic media.